1982
DOI: 10.1002/aic.690280415
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of phase‐separation data for coal‐conversion systems

Abstract: A multiparameter corresponding-states correlation is applied to describe fossil-fluid vapor/liquidequilibrium behavior needed to design separation and other process units in coal-liquefaction plants. Data for both defined and undefined fluids pertinent to coal liquefaction are utilized in correlation development. The procurement of these data requires a thorough evaluation and study of the needs for additional data to improve correlations. These needs are systematically outlined in the context of the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The application of these petroleum-based correlations, however, often leads to unacceptable errors because of the extreme conditions and much higher aromatic content of the coal liquids. This has led to several attempts to develop specific correlations for coal liquids [1][2][3]. These studies have revealed a need for more experimental data on model coal compounds and their mixtures.…”
Section: Introducfionmentioning
confidence: 99%
“…The application of these petroleum-based correlations, however, often leads to unacceptable errors because of the extreme conditions and much higher aromatic content of the coal liquids. This has led to several attempts to develop specific correlations for coal liquids [1][2][3]. These studies have revealed a need for more experimental data on model coal compounds and their mixtures.…”
Section: Introducfionmentioning
confidence: 99%
“…These parameters are generally developed in-house or collected from various literature sources (e.g., [22,23,25,26]). The efforts to develop binary interaction parameters in-house are very significant.…”
Section: Thermophysical Property Data and Process Simulationmentioning
confidence: 99%